Elucidating the Role of Tolerogenic Dendritic Cells in Immune Tolerance and Disease Progression in Multiple Myeloma - Ishibashi, Mariko; Sunakawa-Kii, Mika; Yamaguchi, Hiroki; Morita, Rimpei; Tamura, Hideto (Blood, 2023)
Introduction: Previous research has demonstrated that programmed death-ligand 1 (PD-L1) in multiple myeloma (MM) cells not only suppresses anti-tumor immune responses but also enhances malignant potential through the PD-L1-PD-1 interaction [Ishibashi M, et al. Cancer Immunol Res. 2016]. However, it has not yet been shown that monotherapy and combination therapies utilizing PD-1/PD-L1 antibodies are sufficiently effective for MM. One reason for this is the absence of myeloma-specific cytotoxic T lymphocytes induction in the MM tumor microenvironment. In certain cancers, tumor-infiltrating dendritic cells (DCs) undergo conversion into tolerogenic DCs, which are crucial for inducing and maintaining T-cell tolerance, although this remains unclear in MM. Thus, this study aimed to investigate the function and induction mechanisms of tolerogenic DCs in the MM microenvironment. Materials and Methods: (1) Flow cytometry (FCM) was employed to assess the two conventional DC (cDC; lineage negative, HLA-DR +CD11c high) subsets, cDC1 (CD141 + cDC) and cDC2 (CD1c + cDC), in bone marrow (BM) samples obtained from MM patients (n=17) and healthy controls (n=13). (2) CD14 + monocytes were cultured with IL-4 and GM-CSF to generate monocyte-derived DCs (moDCs). Simultaneously, moDCs were co-cultured with MM cell lines using a trans-well system. The characteristics and functions of moDCs were analyzed using real-time PCR, RNA-sequencing (RNA-seq), western blotting, ELISA, and FCM after lipopolysaccharide stimulation. Results: The frequency of cDC1 subsets was significantly lower in MM patients compared to controls, while the major cDC2 subset did not differ. Similarly, when moDCs were co-cultured with MM cells, moDC numbers were markedly reduced. These co-cultured moDCs exhibited downregulated expression of activation markers CD80, CD86, and CD83, along with decreased phosphorylation of ERK and S6K. Conversely, these moDCs upregulated the expression of immunosuppressive factors IL-10, ARG1, and NOS2 through increased transcription factor C/EBPβ. Moreover, these moDCs inhibited T-cell proliferation, activation, and interferon-γ production in comparison to control moDCs, indicating the presence of immature and tolerogenic phenotypes. However, these phenotypes were not observed in moDCs co-cultured with soluble factors secreted from MM and stromal cells. Treatment with AZD3965 improved the phenotype of moDCs co-cultured with MM cells, reversing their suppressive effect on T-cell proliferation. AZD3965 targets monocarboxylate transporter 1 (MCT1) in MM cells, thereby suppressing extracellular lactate accumulation and acidic pH in the MM microenvironment. Furthermore, RNA-seq analysis comparing moDCs co-cultured with and without MM cells revealed downregulation of gene sets associated with activated DCs in moDCs co-cultured with MM. Notably, moDCs co-cultured with MM showed high enrichment of gene sets related to lysosome biogenesis and NOD-like receptor signaling. This suggests that inflammasome activation in these moDCs leads to caspase-1 activation, resulting in increased levels of mature IL-1β and IL-18 in their cell culture supernatants. Additionally, co-culturing CD38-positive MM cells with CD203a/CD73-positive HS-5 stromal cells and NAD + resulted in the generation of adenosine in the cell culture supernatant. Adenosine promotes the immaturation of mature DCs; however, inflammasome activation does not occur in these DCs. Conclusions: Patients with MM exhibit a reduced frequency of cDC1 subsets, which are crucial for cross-presentation to CD8 + T cells. moDCs in acid pH conditions derived from MM cells display an immature phenotype and impaired function due to decreased DC activation signals. Furthermore, inflammasome activation promotes the secretion of IL-1β and IL-18, contributing to pro-tumorigenic inflammation in the MM microenvironment. Moreover, adenosine generated via the CD38/CD203a/CD73 adenosinergic pathway promotes the immaturation and dysfunction of moDCs. Thus, the characteristics of tolerogenic DCs may vary depending on the MM microenvironment. These findings highlight the induction of tolerogenic DCs by the metabolic microenvironment in MM, leading to immune tolerance and disease progression. Ishibashi:GlaxoSmithKline japan: Research Funding. Tamura:Ono Pharmaceutical Co.: Speakers Bureau; Sanofi K.K.: Speakers Bureau; Chugai Pharmaceutical Co.: Speakers Bureau; Jansen Pharmaceutical K.K.: Speakers Bureau; Bristol Meyers Squib: Speakers Bureau; Takeda Pharmaceutical Co.: Speakers Bureau; Asahi Kasei Pharma.: Research Funding.